2008
DOI: 10.5400/jts.2008.v13i3.209-216
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Tithonia Diversifolia pada Tanah Sawah yang Dipupuk P Secara Starter terhadap Produksi serta Serapan Hara N, P, dan K Tanaman Padi

Abstract: The research of Tithonia diversifolia utilization in the paddy soil that was fertilized P-starter on yield and N, P, K uptake on rice crop, has been conducted from August to December 2005.  The objective of this research was to determine interaction between P-starter levels, and tithonia levels on production and N, P, K element uptake of rice crop. The research was pot experiment in the green house in factorial design 4 x 4.  First factor was 4 levels of tithonia with reduce dosage fertilizer aplied (T0 = 0 t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The sooner the OM decomposed in soil is assumed to be needed a small amount of using synthetic fertilizers. Gusnidar and Prasetyo (2008) reported that the mixture of OM from tithonia and rice straw had not increased the criteria of total N of the soil which was high (0.57%). According to, Francinsco et al (2004) organic N will decompose into mineral N and increase soil N content.…”
Section: Soil Chemical Characteristics After a 3-week Om Incorporationmentioning
confidence: 97%
See 1 more Smart Citation
“…The sooner the OM decomposed in soil is assumed to be needed a small amount of using synthetic fertilizers. Gusnidar and Prasetyo (2008) reported that the mixture of OM from tithonia and rice straw had not increased the criteria of total N of the soil which was high (0.57%). According to, Francinsco et al (2004) organic N will decompose into mineral N and increase soil N content.…”
Section: Soil Chemical Characteristics After a 3-week Om Incorporationmentioning
confidence: 97%
“…Tithonia as an OM source containing 2.5-4 % N and K could substitute Urea and KCl fertilizer (Jama et al 2000;Supriyadi 2003;Hakim and Agustian 2005;Gusnidar 2007). Gusnidar and Prasetyo (2008) found that rice straw contained N, P, K, Ca and Mg which contribute to plant nutrients in soils as well as to slower the diminish of Si and K soil. Additionally, Departemen Pertanian (2004) stated that rice straw could also enhance organic C, exchangeable K and Mg, CEC, as well as available Si in the soil.…”
Section: Plant Height Total Seedlings and Total Paniclesmentioning
confidence: 99%
“…Sebelumnya Takijima dan Sakuma (1961 dalam Situmorang dan Sudadi, 2001) mengemukakan bahwa berdasarkan kinetik, pembentukan AO dalam larutan dengan waktu yang singkat setelah penggenangan, hanya sedikit mempengaruhi pertumbuhan tanaman padi. Supriyadi (2003) serta Gusnidar dan Prasetyo (2008) melaporkan bahwa, titonia mengandung 2,1-3,43 % N; 0,31 % P; 38,5-47,89 % C-total; 9,8 % lignin; 3,3 % polifenol; 2,1-4,16 % K; 1,14-1,30 % Ca; 0,60-0,78 % Mg. Nisbah C/N dan C/P masing-masing 19 dan 128. Lebih lanjut Supriyadi (2003) menemukan AO dalam titonia antara lain 32 mg kg -1 asam sitrat, 11 mgkg -1 asam oksalat, 48 mgkg -1 asam suksinat, 17 mgkg -1 asam asetat, 75 mg kg -1 asam malat, 49 mgkg -1 asam butirat, 31 mgkg -1 asam propionat, 20 mgkg -1 asam phtalat, dan 69 mgkg -1 ; asam benzoat.…”
Section: Pendahuluanunclassified